Keeping track in classroom discourse: Comparing in-service and pre-service teachers' visual attention to students' hand-raising behavior. (July 2023) - Kosel, C.; Böheim, R.; Schnitzler, K.; Holzberger, D.; Pfeffer, J.; Bannert, M.; Seidel, T.
Abstract: This article adds to the understanding of teachers' professional vision by analyzing their gaze in an instructional situation of whole-class discourse using on-action eye-tracking data. We investigated the relationship between pre-service and in-service teachers' attentional processes and students' hand-raising behavior. We found that teachers' attentional processes were positively related to the number of hand-raisings, and that in-service teachers' gazes were more student-centered. Furthermore, in-service teachers were able to distribute their attention among more students, regardless of their hand-raising behavior.